2002
DOI: 10.3346/jkms.2002.17.6.784
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features of Behcet's Disease in Yongdong Districts: Analysis of a Cohort Followed from 1997 to 2001

Abstract: in Yongdong districts in Korea, and to compare the results with the literature. Overall features of clinical manifestations were similar to those described in the literature. However, the frequency of gastrointestinal (GI) ulcerations was much higher than those of other Korean studies. The Korean studies including ours revealed a lower frequency of vascular lesions and epididymitis compared with studies of other countries. The most common site and pattern of inflammatory arthritis were knees and monoarticular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…Whereas the disease is rare in the Western countries [3,29], it occurs with high prevalence in the countries of the ancient Silk Road [30,31], which extends from eastern Asia to the Mediterranean basin [32][33][34]. Epidemiologic investigations have shown that BD has a striking geographic and ethnic distribution, with a particularly high prevalence observed in individuals from Turkish, Japa- nese, or Chinese descent [3,4] and mounting evidence suggests that genetic predisposition might play a crucial role in the development of BD.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas the disease is rare in the Western countries [3,29], it occurs with high prevalence in the countries of the ancient Silk Road [30,31], which extends from eastern Asia to the Mediterranean basin [32][33][34]. Epidemiologic investigations have shown that BD has a striking geographic and ethnic distribution, with a particularly high prevalence observed in individuals from Turkish, Japa- nese, or Chinese descent [3,4] and mounting evidence suggests that genetic predisposition might play a crucial role in the development of BD.…”
Section: Discussionmentioning
confidence: 96%
“…Intestinal BD can result in severe complications, including bowel perforation and extensive hemorrhage, and is therefore one of the major causes of morbidity and mortality in patients with BD8. Intestinal involvement is rare in Mediterranean BD patients (0 to 3%)9, whereas it is relatively more prevalent in East Asia, including Korea and Japan (5–25%)10. Given these geographic and racial differences in the incidence of BD with or without intestinal involvement, intestinal BD is likely to be associated with pathogenic pathways that are distinct from those contributed to BD without intestinal involvement.…”
mentioning
confidence: 99%
“…In addition, the familial aggregation of BD also suggests the strong likelihood of the involvement of genetic factors in developing the disease. A wide range of the BD frequency within families is reported from 2 to 5% in North European countries to 8-15% in endemic areas, such as Middle Eastern countries and Korea [4,8,17]. Moreover, a positive familial history is noted to be more common in pediatric patients than in adult patients (12.3% vs. 2.2%) [18].…”
mentioning
confidence: 87%